Thermal Analysis of Processes at the Solid-Phase Synthesis of Lithium-Titanium Ferrite; Russian Journal of Physical Chemistry A; Vol. 95, iss. 5 - Nikolaev E. V. Evgeny Vladimirovich (2021, 2021)
Title screen